Aplikasi Penggunaan Alat Pengering Pengganti Oven untuk Pembuatan Herbarium di Kebun Raya Liwa Kabupaten Lampung Barat - Yulianty; Amir supriyanto; Eti Ernawiati; Lili Chrisnawati (Bahasa Indonesia, 2022)
One of the countries with high biodiversity is Indonesia. The potential of existing plants has not been maximally empowered by the community, especially in the Liwa Botanical Gardens. The involvement of the staff in the KRL is very necessary to be able to directly collect the observed plants and make a herbarium. Constraint faced in making herbarium is in the drying process. So far, the herbarium drying process is still being carried out in Department of Biology, University of Lampung. This PKM activity will begin with a pre-test to determine the initial ability of KRL staff on the importance of the drying process and the practice of making simple herbarium dryers instead of ovens. At the end of the activity, KRL staff were given a post-test to determine the increase in knowledge about the importance of drying herbariums. With this PKM activity, KRL staff increase their knowledge and skills in using simple tools for drying plant samples and in the long term the availability of more diverse herbariums in an effort to conserve potential plants in KRL. The result of this activity was an increase in score points by 28.08 and a percentage increase in knowledge of 51.63%.